Analysis of the Impact of Parental Divorce on Adolescent Confidence - Batubara, Ummi Khairani; Jasman, Jasman; Murisal, Murisal; Dewita, Erna (Darussalam: Journal of Psychology and Educational, 2022)
This research is motivated by parental divorce which has an impact on adolescent self-confidence. Based on preliminary observations, it was shown that some teenagers experienced the impact of their parents' divorce on their self-confidence, such as closing themselves off, being shy, having difficulty interacting socially. While the purpose of this study is to describe self-confidence from the aspect of social interaction, independence and an optimistic attitude. The research method used is qualitative with a case study approach. The subject of this research is adolescent victims of parental divorce. How to collect data with non-probability sampling technique with a purposive sampling approach. Data collection techniques in this study are observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation, and verification or conclusions. The results of this study from the aspect of social interaction that some teenagers are able to interact socially but some are not. As for the aspect of independence, it shows that in general adolescents are independent in terms of economics, but there are adolescents who are not independent in terms of education. Meanwhile, from the aspect of an optimistic attitude, it shows that teenagers have high optimism to achieve their goals and success in the future, but there are also teenagers who are resigned to the situation that is happening, and do not have a distant view of the future.